Housing the new Romans : architectural reception and classical style in the modern world - Macaulay-Lewis, Elizabeth; Macaulay-Lewis, Elizabeth; Stackelberg, Katharine T. von; Stackelberg, Katharine T. von (Oxford University Press, 2017)
In the last 20 years, reception studies have significantly enhanced our understanding of the ways in which Classics has shaped modern Western culture, but very little attention has been directed toward the reception of classical architecture. 'Housing the New Romans' addresses this gap by investigating ways in which appropriation and allusion facilitated the reception of Classical Greece and Rome through the requisition and redeployment of classicizing tropes to create neo-Antique sites of 'dwelling' in the 19th and early 20th centuries. The volume, across nine essays, will cover both European and American iterations of place making, including Sir John Soanes' house in London, the Hotel de Beauharnais in Paris, and the Getty Villa in California